Non-Newtonian Effects of Blood Flow on Hemodynamics in Pulmonary Stenosis: Numerical Simulation - Fan He; Xinyu Wang; Lu Hua; Tingting Guo (Applied Bionics and Biomechanics)
This paper aims to explore the construction of an individualized pulmonary artery stenosis model based on computed tomography (CT) images. The stenosis model is simulated using a porous medium, and the numerical simulation is carried out by computational fluid dynamics (CFD) method to discuss non-Newtonian effects on hemodynamics. The hemodynamic parameters and quantitative pulmonary pressure ratio (QPPR) of the right pulmonary artery stenosis are obtained. The change curves of hemodynamic parameters show that the effects of non-Newtonian fluid are more significant than those of Newtonian fluid. Under the non-Newtonian condition, pressure and velocity drop more and faster when blood flow enters into the stenosis region. There is a high wall shear stress in the stenosis downstream. The margin of error between the QPPR value of the non-Newtonian fluid simulation and the clinical measurement value is not more than 10%. This work provides the evidence that the simulation of non-Newtonian fluid is closer to the reality when a porous medium model is used in a stenosis model. This contributes to assessing the severity of pulmonary stenosis behavior and is essential to guide disease treatment.